2016
DOI: 10.1016/j.jalz.2015.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous sex hormones and cognitive function in older women

Abstract: INTRODUCTION We examined the association between endogenous sex hormones and both objective and subjective measures of cognitive function. METHODS We followed 3,044 women up to 23 years in a prospective cohort study. We measured plasma levels of estrone, estrone sulfate, estradiol, androstenedione, testosterone, dehydroepiandrosterone (DHEA), and dehydroepiandrosterone sulfate (DHEA-S) in 1989–1990, conducted neuropsychologic testing in 1999–2008, and inquired about subjective cognition in 2012. RESULTS Ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 38 publications
2
14
1
2
Order By: Relevance
“…Estrogen replacement therapy is widely used to reduce cognitive deficits in menopausal women [63]. Koyama et al [64] showed a positive correlation between higher plasma estrogen and better cognitive performance. These results suggest that sex hormones might play a role in the sexual dimorphism of chronic pain-associated cognitive deficits observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen replacement therapy is widely used to reduce cognitive deficits in menopausal women [63]. Koyama et al [64] showed a positive correlation between higher plasma estrogen and better cognitive performance. These results suggest that sex hormones might play a role in the sexual dimorphism of chronic pain-associated cognitive deficits observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of sex differences on multi-compound scores was sometimes reported in the literature [73], but not systematically [56]. Proposed mechanisms to explain sex effect might involve hormonal differences [74], genetic factors, differences in brain networks, socioeconomic roles, and health choices [75].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, several studies have identified associations between baseline DHEA(S) levels and cognitive function, although the direction of the association may differ depending on the population studied and the measures used. In an epidemiologic cohort study, older women with higher plasma DHEA(S) levels were found to be at increased odds of reporting subjective cognitive concerns, whereas in patients with bipolar disorder, serum DHEAS levels were found to be inversely correlated with verbal memory . In contrast, male cancer survivors with lower DHEAS levels were found to perform worse on the attention measure in a cross‐sectional study .…”
mentioning
confidence: 94%